Mineral bone density comparative assessment in patients with systemic lupus erythematosus treated and not treated with glucocorticoids - L A Archakova; N M Kosheleva; A V Smirnov; Z S Alekberova (Научно-практическая ревматология, 2004)
Objective. To compare bone mineral density (BMD) in pts with systemic lupus erythematosus (SLE), treated and untreated by glucocorticoids (GC). Matherial and Methods. 30 females with reliable SLE were examined (APA, 1982), 15 had GC (prednisolone 7.5-60mg/day, median cumulative dose 10.7±6.6g) (1st group), 15 others did not take GC (2nd group). Groups were comparable by age, SLE course duration, body weight. All were females with normal menses period. BMD was assessed in low back vertebral region and femoral neck in standard projections on dichromatic X-ray densitometer QDR-1000 Plus (Hologic, USA) in absolute values (g/cm2) and T-index. Results. BMD in low back was statistically reliably lower in the 1st group as compared with the 2nd (0,918±0,118 and 1,036±0,156; p=0,027). In the left femoral neck there were no differences in mineralization of bone tissue (0,769±0,167 and 0,807±0,227; p=0,568), BMD decreasing in the studied bone region reliably prevailed among pts of the 1st group (n=ll) as compared with the 2nd (n=2) (p=0.003). Conclusion. SLE pis treated by GC demonstrated reliably lower indices of BMD in LI-L4 as compared with pts who were not treated by GC.